2018
DOI: 10.3390/molecules23040839
|View full text |Cite
|
Sign up to set email alerts
|

A Beneficial Role of Rooibos in Diabetes Mellitus: A Systematic Review and Meta-Analysis

Abstract: In a rapid increase in cases of diabetes mellitus worldwide, there has been interested in the use of plant-derived polyphenols as nutraceuticals to prevent the onset and progression of diabetes mellitus and its associated complications. Aspalathus linearis, commonly known as rooibos, is a rich source of uncommon glycosylated plant polyphenols with various critical health-promoting properties, including the prevention and treatment of diabetes mellitus (DM). This study aimed to examine these effects by meta-ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…[ 12 ] Several studies have reported a beneficial role of rooibos extract or its components in diabetes. [ 13 ] Rooibos tea is a popular caffeine‐free beverage and a rich source of polyphenols, with as major component the dihydrochalcone C‐glucoside aspalathin, which is unique to the rooibos plant Aspalathus linearis . [ 14 ] Aspalathin has been attributed anti‐hyperglycemic and cardioprotective effects and is considered a potent anti‐oxidant.…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 ] Several studies have reported a beneficial role of rooibos extract or its components in diabetes. [ 13 ] Rooibos tea is a popular caffeine‐free beverage and a rich source of polyphenols, with as major component the dihydrochalcone C‐glucoside aspalathin, which is unique to the rooibos plant Aspalathus linearis . [ 14 ] Aspalathin has been attributed anti‐hyperglycemic and cardioprotective effects and is considered a potent anti‐oxidant.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes affecting millions of people worldwide is characterized by high blood glucose levels, insulin resistance or insufficiency. Some of the complications responsible for the mortality are considered as triopaty (retinopathy, neuropathy and nephropathy), dyslipidemia and cardiovascular diseases (5,39). In recent years, there has been a growing interest in the use of various alternative products for the treatment and prevention of diabetes (3,4,20,39,42).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the complications responsible for the mortality are considered as triopaty (retinopathy, neuropathy and nephropathy), dyslipidemia and cardiovascular diseases (5,39). In recent years, there has been a growing interest in the use of various alternative products for the treatment and prevention of diabetes (3,4,20,39,42). Melatonin depend on its many physiological effects has been used as an option in preventions of diabetes and its complications (28,43).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence emerging from recent scientific endeavours supports the ability of rooibos phytochemicals to modulate numerous cellular and molecular targets ( Lawal et al, 2019 , Dludla et al, 2017 , Mazibuko-Mbeje et al, 2019 ), hence its potential as an early intervention or possible therapeutic option to several diseases including certain cancers, diabetes and cardiovascular disease ( Sasaki et al, 2018 , Marnewick et al, 2009 , Joubert and de Beer, 2011 , Marnewick et al, 2011 ). Human studies looking at the health benefits of rooibos and the bioavailability of rooibos phytochemicals are scarce but reports have concluded that bioavailability is sufficient to elicit beneficial responses in humans ( Marnewick et al, 2011 ).…”
Section: Bioavailability and Bioactivity Of Rooibosmentioning
confidence: 99%